FPGA Implementation of a Resource Efficient Vedic Multiplier using SPST Adders - Gowreesrinivas, K. V.; Srinivas, Sabbavarapu; Samundiswary , Punniakodi (Engineering, Technology & Applied Science Research, 2023)
Nowadays, the requirement for very high-speed operations in processors constantly increases. Multiplication is a crucial operation in high power-consuming processes such as image and signal processing. The main characteristics of a multiplier are good accuracy, speed, reduction in area, and little power consumption. Speed plays a major role in multiplication operations, and an increase in speed can be obtained by reducing the number of steps involved in the computation process. Since a multiplier has the largest delay among the basic blocks in a digital system, the critical path is determined by it. Furthermore, the multiplier consumes more area and dissipates more power. Hence, designing multipliers that offer high speed, lower power consumption, less area, or a combination of them is of prime concern. Hence, an attempt is made in this paper to achieve the above design metrics using a Spurious Power Suppression Technique (SPST) adder. A resource-efficient SPST-based Vedic multiplier is developed and implemented using Artix 7 FPGA and is finally compared with the ripple carry adder-based Vedic multiplier.